Effect of suction pressures on cell yield and functionality of the adipose-derived stromal vascular fraction. Issue 2 (February 2017) - Chen, Yuan-Wen; Wang, Jing-Ru; Liao, Xuan; Li, Sheng-Hong; Xiao, Li-Ling; Cheng, Biao; Xie, Guang-Hui; Song, Jian-Xing; Liu, Hong-Wei
Summary: Objective: The present study was performed to explore the effect of suction pressures on the cell yield of adipose-derived stromal vascular fraction (SVF) and the functionality of adipose-derived stem cells (ADSCs), situated in the SVF, and to develop optimal parameters of harvesting SVF for clinical use. Methods: Adipose tissue was harvested from the lower abdomen of 10 patients by suction-assisted lipoplasty. Suction pressure was either −30 ± 5 kPa or −55 ± 5 kPa. The aspirated samples were subjected to macroscopic observation to verify the adipose particle size and cytological analysis to detect the cell yield and functionality of the SVF harvested. Results: Adipose tissue harvested at −30 ± 5 kPa appeared to have smaller particle sizes and less blood red cells than that harvested at −55 ± 5 kPa. Cell counts revealed that the cell number of the SVF obtained at −30 ± 5 kPa was more than 2-fold higher than that obtained at −55 ± 5 kPa. Cell growth at passages 1 and 2 was faster at −30 ± 5 kPa than that at −55 ± 5 kPa. The secretion of basic fibroblast growth factor and vascular endothelial growth factor as well as the capacity for adipogenic differentiation of the cultured cells at passages 1–3 were higher at −30 ± 5 kPa than those at −55 ± 5 kPa. There was no difference in the expression of the phenotypic markers between the two groups. Conclusion: Our data indicate that the pressure for harvesting adipose tissue affects the yield and viability of the SVF. A lower suction pressure is beneficial to harvesting the SVF for clinical use.